Calcium intake is not related to breast cancer risk among Singapore Chinese women. Issue 3 (13th March 2013) - Li, Jingmei; Koh, Woon‐Puay; Jin, Ai‐Zhen; Yuan, Jian‐Min; Yu, Mimi C.; Butler, Lesley M.
<x xml:space="preserve">Abstract</x> There is experimental evidence that calcium protects against breast cancer development. Prospective epidemiologic studies supporting a protective effect of calcium on breast cancer risk have mainly been limited to Western populations. We examined the association between calcium intake and breast cancer risk in the Singapore Chinese Health Study, a large population‐based prospective cohort. Calcium intake and supplement use was assessed by in‐person interviewer using a validated food frequency questionnaire. After a mean follow‐up of 14.2±3.5 years, 823 cohort participants developed invasive breast cancer. Multivariate proportional hazards regression models were fitted to examine the associations between calcium intake and breast cancer risk. Vegetables were the primary food source of calcium in this study population, followed by dairy products, grains and soy foods. Calcium intake was not associated with breast cancer risk, comparing highest quartile (>345.6 mg/1, 000 kcal/day) to lowest quartile (<204.5 mg/1, 000 kcal/day) of intake. There was no evidence of effect modification by menopausal status, body mass index, dietary vitamin D or stage of disease at diagnosis. Our findings do not support a hypothesis for calcium in breast cancer chemoprevention, contrary to findings from previous studies among Western populations with higher calcium intake primarily from dairy products and supplements.